Is Oxidized Zirconium Femoral Head Superior to Other Bearing Types in Total Hip Arthroplasty? A Systematic Review and Meta-Analysis. - Malahias, Michael-Alexander; Atrey, Amit; Gu, Alex; Chytas, Dimitrios; Nikolaou, Vasileios S; Waddell, James P (J Arthroplasty, 2019)
BACKGROUND: Oxidized zirconium (OxZi) is a relatively new type of material that combines the strength of a metal with the surface/wears properties of a ceramic. Our aim was to investigate whether OxZi femoral heads lead to lower polyethylene wear, higher survival rate, and better clinical outcomes than the other bearing types in patients treated with total hip arthroplasty (THA). METHODS: Two reviewers independently conducted a systematic search according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses using the MEDLINE/PubMed database and the Cochrane Database of Systematic Reviews. These databases were queried with the terms: a. "oxidized" AND "zirconium" AND "total" AND "hip" AND "arthroplasty"; b. "oxinium" AND "total" AND "hip" AND "arthroplasty". The primary outcome measures were the survival rate of the bearing surfaces as well as the polyethylene wear. RESULTS: The vast majority (85.7%) of the studies, which reported the mean polyethylene wear rate, showed that there was not any significant difference between OxZi and cobalt-chrome (CoCr) femoral heads (rate ratio: 0.836; 95% confidence interval: 0.362-1.928; P = .674). All studies comparing the survival rate of OxZi and CoCr femoral heads illustrated almost excellent survivorship with both implants. CONCLUSION: OxZi femoral heads did not lead to lower polyethylene wear rate or higher survival rate, when compared with CoCr femoral heads in patients treated with THA. On the basis of these results and taking into account the higher cost of these implants, we would not recommend the routine use of OxZi femoral heads in primary THAs. LEVEL OF EVIDENCE: Systematic review and meta-analysis of therapeutic studies I-III.